2022
DOI: 10.3390/ijerph19084698
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequalities in Women’s Undernutrition: Evidence from Nationally Representative Cross-Sectional Bangladesh Demographic and Health Survey 2017–2018

Abstract: The objective of this study was to explore the socioeconomic inequalities in undernutrition among ever-married women of reproductive age. We used nationally representative cross-sectional data from the Bangladesh Demographic and Health Survey, 2017–2018. Undernutrition was defined as a body mass index (BMI) of <18.5 kg/m2. The concentration index (C) was used to measure the socioeconomic inequality in the prevalence of women’s undernutrition. A multiple binary logistic regression model was carried out to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
4
2
0
Order By: Relevance
“…According to data from the Bangladesh Demographic and Health Survey, 2017–18, the overall prevalence of women’s undernutrition in Bangladesh was reported as 12 percent. This finding aligns with a previous study conducted in Bangladesh [ 11 ]. Examining the residential aspect, it is evident that the prevalence of undernutrition among ever-married women in Bangladesh is higher in rural residences (13.3 percent) compared to urban residences (8.6 percent).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…According to data from the Bangladesh Demographic and Health Survey, 2017–18, the overall prevalence of women’s undernutrition in Bangladesh was reported as 12 percent. This finding aligns with a previous study conducted in Bangladesh [ 11 ]. Examining the residential aspect, it is evident that the prevalence of undernutrition among ever-married women in Bangladesh is higher in rural residences (13.3 percent) compared to urban residences (8.6 percent).…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate the presence of socioeconomic disparities in the prevalence of undernutrition among ever-married women of reproductive age in Bangladesh, consistent with findings observed in other low- and middle-income countries [ 25 ]. These conclusions align with a previous study conducted in Bangladesh, which also highlighted the disproportionate vulnerability of women from lower-income households to undernourished compared to their counterparts from rich families [ 11 ]. Similar results have been reported in other studies conducted in Tanzania and Ethiopia, with the state of malnutrition decreasing as the wealth index increases [ 24 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Earlier studies have reported that the prevalence of the double burden of household‐level malnutrition was high in LMICs (Doku & Neupane, 2015 ; Onyango et al, 2019 ). We estimate the prevalence of undernutrition to be approximately 12% women in Bangladesh being underweight, which was consistent with another recent study conducted in Bangladesh (Rahman et al, 2022 ). Compared to undernutrition, approximately 33% women experienced overnutrition (i.e., overweight and obese), which was higher than several South Asian countries (He et al, 2016 ; Hong et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%